Evita el agotamiento (Assemble You, 2022)
Welcome to Audio Learning by Assemble You. According to an Indeed survey in 2021, more than half of employees suffer from burnout. Officially recognized by the World Health Organization in 2019 as an occupational disease, burnout is characterized by symptoms including emotional exhaustion, skepticism, and inefficacy, and has been linked to mental and physical health problems including, but not limited to, increased risk of coronary heart disease, depression and anxiety. In this recording, our goal is to provide a better understanding of burnout, and to offer multiple key practical techniques to help alleviate it. Learning Objectives Learn what burnout is and what lies behind it Learn practical techniques to limit the negative effects of burnout and how to prevent it.